PENINGKATAN KOMPETENSI GURU PEMBINA OLIMPIADE MATEMATIKA SISWA SEKOLAH MENENGAH PERTAMA KABUPATEN MADIUN - Mohammad Tohir (As-Sidanah, 2019)
The objective of this research is to describe the improvement of the competence of Olympic workshop participants in problem-solving of mathematics Olympiad for mathematics teachers of Junior High Schools in the Madiun Regency by using the qualitative descriptive approach. The subjects of this research were 66 participants of junior high school mathematics teachers workshop organized by Mathematics teachers in each junior high school or MGMP in collaboration with the Depatment of Education and Culture of Madiun Regency. The data collection were carried out with a written test in the description form consisting the results of pre-test, post-test, practice questions, presentations from each group and observation results during the workshop. The results indicated that the mathematics Olympiad workshop activities for Junior High School mathematics teachers in Madiun Regency could increase the understanding of workshop participants in solving mathematics Olympiad questions. This improvement could be seen from the answers of practice questions as well as from the presentations session whereas the teachers could clearly describe several topics such as an algebraic, number theory, geometry, combinatorics, and statistics. However, an advanced Olympics workshops are still needed to help the teachers of Junior High School mathematics Olympiad in Madiun Regency.